Delineando os saberes da geografia escolar no curso técnico em meio ambiente do IFMA - Campus Buriticupu: projeto de trabalho uma proposta integradora - SILVA, Jucileide Melonio Pereira (2020)
This study is originated from reflections on School Geography and its contributions to professional training. The research had as general objective to build a work project as an integrative practice from the teaching of Geography in the technical course in Environment of the Federal Institute of Education, Science and Technology of Maranhão. The specific objectives were: to identify the implications of School Geography for technical training in the Environment; to ascertain which geographic and environmental themes can be developed in a qualitative way contributing to the training of students and helping teaching practice; elaborate a work project as an integrative practice that allows the articulation of geographic, environmental and other areas. The methodology used was a qualitative approach, which constituted as an instrumental case study based on André (2005), Martins (2008) and Mazzotti (2006). The bibliographic research addresses School Geography based on Cavalcanti (2012), Callai (2000), Vlach (2004) and Vesentini (2004). About integrated curriculum, interdisciplinarity and work project, this research was based on Santomé (1998), Fazenda (2008), Hernández; Ventura (1998), and to substantiate the discussions on Professional Education, Ramos (2019), Cunha (2000; 2005) and Manfredi (2002) were the bases. The instruments used in the data production were observations held on the buildings of the studied institution and during the other research activities; interviews addressed to teachers and educators; and questionnaires applied to senior students of the course under study. To assess the data produced, we used the interpretative descriptive analysis, through which we describe the participants' reports and interpret them in the light of the theorists selected for such study. The research showed that Geography in collaboration with other disciplines can promote meaningful and articulated learning with reality, in addition to demonstrating the relevance of the collective work of teachers for the integrated curriculum, highlighting interdisciplinary activities as a way to promote more significant teaching, capable of awakening in students different perspectives of knowledge appropriation. The production of the data helped in the elaboration of the work project proposal for the Technical Course in Environment of IFMA/Buriticupu.